Pengaruh Religiusitas, Love of Money, dan Keadilan Sistem Perpajakan terhadap Penggelapan Pajak - Chaerul Meizar; Donny Indrawan; Dien Noviany Rahmatika (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
Tax is an important source of income for the state because it plays a major role in the development of the country. However, taxes that must be paid through tax evasion violations must still be reduced. Indonesians are very social, so that increasing tax evasion is considered normal, especially for matters relating to personal taxes. This study investigates how religiosity, love of money, and fairness of the tax system impact tax evasion. This study uses a Structural Literature Review (SLR) to systematically analyze a number of articles published from 2018 to 2024. The literature is categorized based on relevant concepts and then grouped as incongruent themes to discuss additional issues about the influence of religiosity, love of money, and fairness of the tax system on tax evasion. The results and discussion show that Religiosity, Love of Money, and Fairness of the Tax System have a significant effect on tax evasion.